The effect of vocabulary learning strategies in enhancing vocabulary learning among secondary school students in Bani-Walid Libya - Almabrouk, Salma Hasan (2017)
Studies have shown that vocabulary learning strategies (VLS) have an essential role in improving vocabulary knowledge among non-native learners of English.However in Libya, studies on the effect of using vocabulary learning strategies to enhance vocabulary knowledge are still lacking. Studies have also revealed that there is a weak performance in vocabulary learning and vocabulary knowledge among secondary school students. This study investigated the effect of vocabulary learning strategies in enhancing vocabulary knowledge among secondary school students in Bani-Walid, Libya. It also explored students’ feedback on types of vocabulary learning strategies the students used before and after the intervention. The instruments used were questionnaire, vocabulary test, semi-structured interviews and logbooks. The independent sample t-test, descriptive statistics, and thematic analysis were employed to analyse the data. The VLS questionnaires were distributed to 280 secondary school students, and the pre-tests and post-tests of vocabulary were administered to 80 secondary school students in the experimental and control groups. The experimental group received the treatment for eleven weeks using VLS, whereas the control group was taught using the traditional method. Meanwhile, the semi-structured interviews were conducted with twelve students, and logbooks were distributed to six students. The findings showed a significant difference in vocabulary test scores between the experimental and control groups. The findings showed a positive influence on the vocabulary learning strategies in enhancing vocabulary knowledge among the learners in Libya. The results also indicated that the memory strategies had a significant effect in enhancing vocabulary learning among these learners. The findings propose that the curriculum include training Libyan teachers to integrate vocabulary learning strategies in the vocabulary teaching.